Gain-of-function DNMT3A mutations cause microcephalic dwarfism and hypermethylation of Polycomb-regulated regions. (January 2019) - Heyn, Patricia; Logan, Clare; Fluteau, Adeline; Challis, Rachel; Auchynnikava, Tatsiana; Martin, Carol-Anne; Marsh, Joseph; Taglini, Francesca; Kilanowski, Fiona; Parry, David; Cormier-Daire, Valerie; Fong, Chin-To; et al.
Abstract DNA methylation and Polycomb are key factors in the establishment of vertebrate cellular identity and fate. Here we report de novo missense mutations inDNMT3A, which encodes the DNA methyltransferase DNMT3A. These mutations cause microcephalic dwarfism, a hypocellular disorder of extreme global growth failure. Substitutions in the PWWP domain abrogate binding to the histone modifications H3K36me2 and H3K36me3, and alter DNA methylation in patient cells. Polycomb-associated DNA methylation valleys, hypomethylated domains encompassing developmental genes, become methylated with concomitant depletion of H3K27me3 and H3K4me3 bivalent marks. Such de novo DNA methylation occurs during differentiation ofDnmt3a W326R pluripotent cells in vitro, and is also evident inDnmt3a W326R/+ dwarf mice. We therefore propose that the interaction of the DNMT3A PWWP domain with H3K36me2 and H3K36me3 normally limits DNA methylation of Polycomb-marked regions. Our findings implicate the interplay between DNA methylation and Polycomb at key developmental regulators as a determinant of organism size in mammals. Gain-of-function mutations altering the PWWP domain of DNMT3A are identified as a new cause of microcephalic dwarfism. These mutations abrogate DNMT3A binding to H3K36me2 and H3K36me3 and lead to aberrant DNA methylation of Polycomb-marked regions.